2014
DOI: 10.1155/2014/280243
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Substance Use Disorder on Presentation and Short-Term Course of Schizophrenia

Abstract: The aim of the present study was to compare a cohort of schizophrenia patients with substance use disorder (SUD) with a similar cohort of schizophrenia patients without SUD with regard to sociodemographic variables, clinical variables, psychopathology, anxiety symptoms, depressive symptoms, treatment outcome, and side effect profile of drugs. A total of 143 consecutive inpatients with ICD-10 DCR diagnosis of schizophrenia were included after obtaining informed consent. Patients were evaluated by a semistructur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…On the other hand, the prevalence of the current study was higher than those of studies done in Addis Ababa, Ethiopia, 20 Nigeria, 12 Sri Lanka, 10 Singapore 6 and India. 21 The discrepancy might be due to most of the indicated studies were measured by using different tools like ASSIST. And the participants were patients with bipolar disorders, and depression and schizophrenia in the Addis Ababa’s and Singapore’s studies, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the prevalence of the current study was higher than those of studies done in Addis Ababa, Ethiopia, 20 Nigeria, 12 Sri Lanka, 10 Singapore 6 and India. 21 The discrepancy might be due to most of the indicated studies were measured by using different tools like ASSIST. And the participants were patients with bipolar disorders, and depression and schizophrenia in the Addis Ababa’s and Singapore’s studies, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Again, it can result in non-adherence to treatments, relapse of psychiatric disorders, an increase in the cost of health care, and the reduction of the quality of life among patients with severe mental disorders. 21 , 22 , 32 Researchers reported that younger age, 15 , 20 male sex, 10 , 18 being unmarried, 13 low educational level, 10 , 20 unemployment, 10 , 33 longer duration of illness, 30 , 34 early age of onset of illness, 34 , 35 and having schizophrenia and/bipolar disorders 12 , 15 are the main factors that influence individuals with severe mental disorders to have AUD. Having poor social support, 10 , 11 high perceived stress, 11 use of other psychoactive substances like tobacco smoking, 6 , 12 , 19 and family history of alcohol and other substance use disorders 16 , 36 are also important contributing factors to AUD among patients with severe mental disorders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies indicate that SMI patients using illicit drug exhibit poorer outcomes in a variety of domains: symptom severity, psychiatric relapse, hospitalization, suicide (40) (41), incarceration, violence and victimization, physical health problems, homelessness (42), extended hospitalization (43), increased healthcare costs, reduced compliance with medications, increase treatment resistance (44), increased depression symptoms (45) and suicide ideation, as well as mania and bipolar disorder(46). The substances mostly studied are cannabis, alcohol and amphetamine but there is no large study on khat effect in people with SMI, but case reports (47) and qualitative study(48) noted that patients with serious mental illness who used khat had their illness exacerbated by the use of it.…”
Section: Introductionmentioning
confidence: 99%
“…The term originated from the USA in the 1980s and has been adopted in the UK more recently. Worsening psychiatri c symptoms , more frequent re hospitalisation , poor physical health, poor medicine adherence and others 13,14 . Studies have documented that treatment compliance can be affected by the concurrent presenc e of substanc e abuse.…”
Section: Introductionmentioning
confidence: 99%